An Overview of Emotional Support and Self-Acknowledgment Among Parents of Children with Special Needs - Despriliani, Ririn; Fatimah, Silvia; Mirawati; Hopiani, Ayu (International Journal of Science and Society, 2024)
This study examines how emotional support functions as a way for parents to accept children with special needs. It is considered important to strengthen the connection between parents and children and help children understand and accept themselves. Data were collected from four parents of children with special needs in a kindergarten in East Bandung through a qualitative research method using interview and questionnaire instruments. The results of the study indicate that parental acceptance of themselves by providing emotional support is very important for children's emotional development. Parents who accept their child's situation tend to share better emotional support, such as affection, support, appreciation, encouragement, involvement in decision-making, and validation of their child's feelings. This support also builds children's self-confidence and makes them feel accepted by their environment. Self-acceptance in parents is a difficult process that involves complex emotional stages ranging from rejection to acceptance. Families and communities have shown that their support is very important to help parents in the process of creating a friendly and supportive environment for children with special conditions.